Digitalisasi ajaran Ki-Hadjar-Dewantara pada proses pembelajaran neo-guided inquiry untuk mengembangkan literasi dan numerasi mahasiswa - Vava Imam Agus Faisal; Nugroho Prasetya Adi (University of Muhammadiyah Malang, 2023)
The demands of the digital era produce students who are digital netive and tend to be anti-social in learning, so there is a need for learning that is humanistic and characterizes Indonesia. The purpose of this research is to find out how to digitize the application of the teachings of Ki-Hadjar-Dewantara in the Neo-Guided Inquiry learning process to develop ideal student literacy and numeracy skills. This research is a classroom action research that adopts the McKernan model that combines quantitative and qualitative methods. Quantitative methods use questionnaires to measure the achievement of learning indicators, self-assessment to see the level of success in applying learning, and assessment sheets to see the results of forming students' literacy and numeracy abilities. Qualitative methods using observation sheets to explore empirically the problems that arise, the process of implementing and evaluating Neo-Guided Inquiry learning. Focus group discussion to collect data on problem description, needs assessment and learning evaluation. The average result of assessing students' literacy and numeracy abilities in the second cycle was 86.4 which was classified as very high, and the practicality level of the self-assessment results of 95.75% was included in the very good category, so that its application was declared very successful.